MEASURING THE DETERMINANTS OF EMPLOYEE PERFORMANCE - Siskya Nanda Prasika; Aprih Santoso (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of motivation, compensation, workload and work environment on employee performance at PT. SDN. This study uses a quantitative research method. The independent variables in this study are motivation, compensation, workload, and work environment, while the dependent variable is employee performance. Sampling in this study using saturated samples, amounting to 58 people. Sampling technique with probability sampling. Data collection using a questionnaire. The analysis used includes descriptive data analysis, quantitative data analysis, validity test, reliability test, classical assumption test, multiple linear regression, and hypothesis testing. The results of this study found that: (1) Motivation has a positive and significant effect on employee performance at PT. SDN. (2) Compensation has a positive and significant effect on employee performance at PT. SDN (3) Workload has a negative and significant effect on employee performance at PT. SDN. (4) The work environment has a positive and significant effect on employee performance at PT. SDN. The discussion, conclusions and suggestions are described in this article. Keywords: motivation, compensation, workload, work environment, employee performance